(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we establish some new Lyapunov type inequalities for fractional (p, q)-Laplacian operators in an open bounded set Ω⊂R^N, under homogeneous Dirichlet boundary conditions. Next, we use the obtained inequalities to derive some geometric properties of the generalized spectrum associated to the considered problem.